Debate on the treatment of multiple sclerosis: Experience from an intractable multiple sclerosis case with rebound syndrome after fingolimod cessation. (14th March 2019) - Kuroda, Hiroshi; Nishiyama, Shuhei; Matsumoto, Yuki; Misu, Tatsuro; Fujihara, Kazuo; Aoki, Masashi
Abstract: Background: Fingolimod is an effective disease‐modifying drug for relapsing–remitting multiple sclerosis (RRMS), but drug discontinuation might cause rebound syndrome, defined as massive and prolonged exacerbation of MS. We report a case of intractable MS with rebound syndrome after fingolimod cessation. Case presentation: A 54‐year‐old patient with RRMS had been disease activity‐free for 9 years during fingolimod treatment. However, she discontinued fingolimod by her own decision out of concern for progressive multifocal leukoencephalopathy. Five weeks after drug cessation, she developed progressive weakness in the left leg. Expanded Disability Status Scale scores worsened from 2.0 to 6.0. Blood tests showed recovery of lymphocyte count (1000/mm 3 ) from the previous counts. Cerebrospinal fluid examination showed almost normal results, except for marked elevation of myelin basic protein (1420 pg/mL). Brain magnetic resonance imaging showed a massive lesion in the right frontal lobe with open‐ring enhancement and a small enhancing lesion in the left parietal lobe. Based on diagnosis as exacerbation of RRMS, the patient was treated with intravenous methylprednisolone, followed by oral dimethyl fumarate. However, 5‐month use of DMF could not remit the disease activity, leading to fingolimod reinitiation. Conclusions: Rebound syndrome is an intractable complication of exit strategy for fingolimod‐treated RRMS patients. To lower the risk for rebound syndrome, specific mechanisms of rebound syndrome are to be clarified. Furthermore, concise risk stratification for progressive multifocal leukoencephalopathy in fingolimod treatment is imperative. Taken together, the risk–benefit analysis for fingolimod treatment, including rebound syndrome as well as progressive multifocal leukoencephalopathy, is required to initiate the drug.